Pengembangan BEGETAR (Bel Gelang Getar) sebagai Isyarat Mengetahui Tamu bagi Penyandang Gangguan Pendengaran - M Ridho; Irdamurni Irdamurni (Jurnal Pendidikan Kebutuhan Khusus, 2023)
This research is motivated by the problem of hearing impaired people in knowing when guests come to the house, so far people with hearing impairments do not respond to signals given by guests. BEGETAR is a bell that is specifically used for people with hearing loss, this tool uses a bracelet that must be used by the user in order to feel the vibration signal given after the guest presses the bell in front of the house. The method that the researchers used in the study developed BEGETAR (Vibrating Bell Bracelet) as a signal to know guests for people with hearing loss using Research and Development research methods. The results of trials and validations carried out with technology experts, design experts, and hearing loss experts found the weaknesses of the products that the researchers developed so that the weaknesses of these products became a reference for researchers to improve the products that the researchers developed in accordance with the validator's directions, so that the expected products were in accordance with usefulness and effectiveness and efficiency of the product that researchers developed to help people with hearing loss identify guests who will come to the house.